Памяти Вячеслава Акимовича Великанова — крупного геолога и замечательного человека - Старостенко, В.И.; Ентин, В.А.; Костенко, Н.М.; Гинтов, О.В. (Геофизический журнал, 2019)
Памяти Вячеслава Акимовича Великанова — крупного геолога и замечательного человека / В.И. Старостенко, В.А. Ентин, Н.М. Костенко, О.В. Гинтов // Геофизический журнал. — 2019. — Т. 41, № 5. — С. 252-254. — рос.